Tanshinone IIA Prevents Uric Acid Nephropathy in Rats through NF-κB Inhibition - Wu, Xinlin; Liu, Lihua; Xie, Hongbo; Liao, Jiantang; Zhou, Xin; Wan, Jianxin; Yu, Kuang; Li, Junbiao; Zhang, Yu (Planta Medica, 2012)
The purpose of this research is to investigate the effect of tanshinone IIA, an extract of the Chinese medicine Que Xie Hua Yu Tang, on uric acid nephropathy (UAN) and to elucidate the underlying mechanisms. UAN rat model was established. Fifty UAN rats were randomly allocated into 5 groups: adenine-treated group, allopurinol-treated group, and low/middle/high dose of tanshinone IIA-treated groups. Meanwhile, another 10 rats were used as normal controls. Serum uric acid (UA), blood urea nitrogen (BUN), serum creatinine (Scr), MCP-1, and IL-1β levels were measured. Histological staining was performed. Comparison between the adenine group and treatment (allopurinol and tanshinone IIA) groups showed compound treatment could attenuate the inflammation status of the kidneys and decrease serum UA levels. Among different kinds of medicine, tanshinone IIA had similar effects as allopurinol and exerted anti-inflammatory and renal protective effect in a dose-dependent manner. Furthermore, we found tanshinone IIA alone could also inhibit urate-induced MCP-1 and IL-1β overexpression both in vivo and in vitro, accompanied with inhibition of NF-κB translocation from cytosome to nucleus. Tanshinone IIA could protect rats from uric acid-induced kidney damage, probably by attenuating renal inflammatory status.
Keywords: tanshinone IIA; uric acid nephropathy; Chinese herb; Salvia miltiorrhiza; Lamiaceae